Islamic Perspective And The Public Awareness In Protecting Of Environment - Situmorang, Muhajirin Ansori (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
In modern lifestyle in this era ,the environmental problems are still an unresolved issue. Nowdays, there are still few humans who care about efforts to protect and preserve the environment. The Humans as thinking beings should be able to implement their behavior in accordance with religious guidance in preserving the environment. Not only taking advantage of the availability of nature, but also being able to manage it as a mandate from God. The aim of this research is to provide a general description and concept of ecological responsibility in an Islamic perspective that refers to its sources, namely the quran and Hadith. As well as providing data on how the current public awareness in maintaining and preserving the environment. In the Quran, it is explicitly stated that humans have ecological responsibilities. Because the creation of humans in the concept of the quran is as Khalifah on earth, which means the role, duties and responsibilities of humans in managing the earth as a place of life. It is not only Islam that teaches about environmental care. But all religions emphasize ethics towards the environment. One of the biggest factors in the lack of public concern in preserving the environment is the lack of knowledge in ecology, both its roles and responsibilities, as well as the concept of management and its impact.